Treatment and generation of electricity from palm oil mill effluent using locally isolated electroactive microbes in microbial fuel cell - Sh. Abdirahman Elmi, Hassan (2014)
Palm oil industries are the largest agricultural based industries in Malaysia and in processing palm oil, high pollutant liquid waste known as palm oil mill effluent (POME) is being generated. Currently, treatment of POME to meet the standard discharge limit and generate environmentally friendly renewable energy has become an important issue. Therefore, this study was conducted to treat final discharge POME in microbial fuel cell (MFC) and generate electricity using electro-active bacteria from palm oil mill sludge (POMS). Double chamber MFC fabricated using polyacrylic sheets with a working volume of 1 L, proton exchange membrane (Nafion 115) and carbon electrodes connected to copper wires attached to a resistor of 10 kO were used. The anodic solution consisted of final discharge pond POME, overnight SRB1 inoculum (10% v/v) and phosphate buffer (pH 7) while the cathodic solution consisted of phosphate buffer (pH 7) and potassium hexacyanoferrate (III). The results showed 58% of COD removal and 60% of colour removal in 8 days. Simultaneously electricity generation was monitored and the maximum voltage, current density, power density and columbic efficiency recorded using a digital multimeter was 942 mV, 89.2 mA/m2, 83.7 mW/m2 and 54% respectively. The SRB1 bacterium that was used to treat the POME and produced electricity was later identified as Pseudomonas aeruginosa strain NCIM 5223 using molecular techniques (16S rDNA analysis). In conclusion SRB1 was able to treat and generate electricity from final pond POME